Comparison of diagnostic efficacy between 99mTc-methylene diphosphate SPECT/CT and MRI for bone and joint infections: a multicenter retrospective analysis - Gao, Hao; Li, Guoquan; Fu, Congxiao; Ren, Jun; Kang, Fei; Luo, Wen; Yin, Qian; Zhou, Cheng; Li, Bo; Lu, Shuaikun; Wang, Hu; Zhang, Yong; et al. (Frontiers in Endocrinology, 2024)
Objective There is currently no non-invasive examination that can fully determine the diagnosis of osteomyelitis. SPECT/CT tomographic fusion imaging can provide both local metabolic activity and anatomical information to determine the condition and location. This study evaluates the diagnostic efficacy of 99mTc-MDP SPECT/CT in bone infections, compared to MRI. Methods In this multicenter retrospective study, 363 patients with suspected bone and joint infections or osteomyelitis were included. Participants underwent 99mTc-MDP SPECT/CT and/or MRI examinations, supplemented by pathogenic bacterial cultures and histopathological analysis. Results Only SPECT/CT was tested in 169 patients, and only MRI was used in 116. 78 people have implemented both inspections and have detailed information. The diagnostic sensitivity and specificity of SPECT/CT for infection were 96% and 92% respectively, with an accuracy of 96%. For MRI, these figures were 88%, 84%, and 87% respectively. Conclusion This represents the largest global study to date evaluating osteomyelitis and bone infection diagnosis using 99mTc-MDP SPECT/CT tomographic fusion imaging. The findings indicate that 99mTc-MDP SPECT/CT fusion imaging offers superior diagnostic accuracy compared to MRI. This is particularly evident in cases involving metallic implants and chronic infections. 99mTc-MDP SPECT/CT fusion imaging emerges as a highly suitable non-invasive diagnostic modality, facilitating enhanced clinical follow-up and treatment.